A shape memory foam composite with enhanced fluid uptake and bactericidal properties as a hemostatic agent. (1st January 2017) - Landsman, T.L.; Touchet, T.; Hasan, S.M.; Smith, C.; Russell, B.; Rivera, J.; Maitland, D.J.; Cosgriff-Hernandez, E.
Graphical abstract: Abstract: Uncontrolled hemorrhage accounts for more than 30% of trauma deaths worldwide. Current hemostatic devices focus primarily on time to hemostasis, but prevention of bacterial infection is also critical for improving survival rates. In this study, we sought to improve on current devices used for hemorrhage control by combining the large volume-filling capabilities and rapid clotting of shape memory polymer (SMP) foams with the swelling capacity of hydrogels. In addition, a hydrogel composition was selected that readily complexes with elemental iodine to impart bactericidal properties to the device. The focus of this work was to verify that the advantages of each respective material (SMP foam and hydrogel) are retained when combined in a composite device. The iodine-doped hydrogel demonstrated an 80% reduction in bacteria viability when cultured with a high bioburden of Staphylococcus aureus . Hydrogel coating of the SMP foam increased fluid uptake by 19× over the uncoated SMP foam. The composite device retained the shape memory behavior of the foam with more than 15× volume expansion after being submerged in 37 °C water for 15 min. Finally, the expansion force of the composite was tested to assess potential tissue damage within the wound during device expansion. Expansion forces did not exceed 0.6 N, making tissue damage during device expansion unlikely, even when the expanded device diameter is substantially larger than the target wound site. Overall, the enhanced fluid uptake and bactericidal properties of the shape memory foam composite indicate its strong potential as a hemostatic agent to treat non-compressible wounds. Statement of Significance: No hemostatic device currently used in civilian and combat trauma situations satisfies all the desired criteria for an optimal hemostatic wound dressing. The research presented here sought to improve on current devices by combining the large volume-filling capabilities and rapid clotting of shape memory polymer (SMP) foams with the swelling capacity of hydrogels. In addition, a hydrogel composition was selected that readily complexes with elemental iodine to impart bactericidal properties to the device. The focus of this work was to verify that the advantages of each respective material are retained when combined into a composite device. This research opens the door to generating novel composites with a focus on both hemostasis, as well as wound healing and microbial prevention.